Chromium plasmonic polarizer for high intensity light - Michalik, Damian Arkadiusz; Jung, Paweł S.; Klus, Bartłomiej W.; Kowalik, Andrzej; Rojek, Anna; Laudyn, Urszula A.; Karpierz, Mirosław A. (Photonics Letters of Poland, 2017)
In this work, we investigate a thin-film polarizer for a high intensity of the electromagnetic (EM) beam based on Cr nano wire arrays. Commonly used thin-film polarizing components are very sensitive for high power of EM waves and can be easily damaged by focused beams. The solution to this problem could be the thin-film polarizer based on metallic subwavelengths structures. This type of optical element has huge resistance comparing to typical thin-film polarizers. However, designing such an optical element for proper wavelength of EM wave and transmissions is not easy task. In this paper we present numerical as well as experimental results for specially designed chromium thin-film polarizer for wavelength 532nm Full Text: PDF References W. Zhou, K. Li, C. Song, P. Hao, M. Chi, M. Yu and Y. Wu, "Polarization-independent and omnidirectional nearly perfect absorber with ultra-thin 2D subwavelength metal grating in the visible region", Opt. Express 23, 11 (2015). CrossRef W. L. Barnes, A . Dereux, and T. W. Ebbesen, "Surface plasmon subwavelength optics", Nature 424, 824-830 (2003). CrossRef C. Lee, E. Sim, D. Kim, "Blazed wire-grid polarizer for plasmon-enhanced polarization extinction: design and analysis", Opt. Express 25, 7 (2017). CrossRef A. Lehmuskero, Metallic thin film structures and polarization shaping gratings (University of Eastern Finland 2010). Y. Leroux, J. C. Lacroix, C. Fave, V. Stockhausen, N. Felidj, J. Grandm, A. Hohenau, J. R. Krenn, "Active plasmonic devices with anisotropic optical response: a step toward active polarizer", Nano Lett. 5, 9 (2009). CrossRef R. T. Perkins, D. P. Hansen, E. W. Gardner, J. M. Thorne, A. A. Robbins, Broadband wire grid polarizer for the visible spectrum, US 6122103 (2000). DirectLink D. M. Sullivan, Electromagnetic simulation using the FDTD method, New York: IEEE Press Series (2000). CrossRef J. P. Berenger, Perfectly Matched Layer (PML) for Computational Electromagnetics, Morgan & Claypool Publishers (2007). CrossRef Yu, W., and R. Mittra, "A conformal FDTD software package modeling antennas and microstrip circuit components", IEEE Antennas Propagat. Magazine 42, 28 (2000) . CrossRef L. W. Bos, D. W. Lynch, "Optical Properties of Antiferromagnetic Chromium and Dilute Cr-Mn and Cr-Re Alloys", Phys. Rev. Sect. B, 2, 4267 (1970). CrossRef